MLH1 germline epimutations as a factor in hereditary nonpolyposis colorectal cancer. - Hitchins, M; Williams, R; Cheong, K; Halani, N; Lin, V; Packham, D; Ku, S; Buckle, A; Hawkins, N; Burn, J; Gallinger, S; Goldblatt, J; et al. (2005)
BACKGROUND and AIMS: Hereditary nonpolyposis colorectal cancer (HNPCC) is caused by heterozygous germline sequence mutations of DNA mismatch repair genes, most frequently MLH1 or MSH2. A novel molecular mechanism for HNPCC has recently been suggested by the finding of individuals with soma-wide monoallelic hypermethylation of the MLH1 gene promoter. In this study, we determined the frequency and role of germline epimutations of MLH1 in HNPCC. METHODS: A cohort of 160 probands from HNPCC families who did not harbor germline sequence mutations in the mismatch repair genes were screened for methylation of the MLH1 and EPM2AIP1 promoters by combined bisulfite and restriction analyses. Allelic expression and family transmission of MLH1 were determined using polymorphisms in intron 4 and the 3' untranslated region. RESULTS: One of 160 individuals had monoallelic MLH1 hypermethylation in peripheral blood, hair follicles, and buccal mucosa, indicative of a soma-wide alteration. Monoallelic transcription of the paternal MLH1 allele was shown using a heterozygous expressed polymorphism within the 3' untranslated region. The hypermethylated allele was maternally transmitted, however, the mother and siblings who inherited the same maternal homologue were unmethylated at MLH1, suggesting the epimutation arose as a de novo event. CONCLUSIONS: Germline MLH1 epimutations are functionally equivalent to an inactivating mutation and produce a clinical phenotype that resembles HNPCC. Inheritance of epimutations is weak, so family history is not a useful guide for screening. Germline epimutations should be suspected in younger individuals without a family history who present with a microsatellite unstable tumor showing loss of MLH1 expression.